PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH DI PT BANK CENTRAL ASIA KCP MASJID JAMIK KOTA PANGKALPINANG - Brigita, Metta; Tri Setyo Mulyani, Hendarti; Oktalina, Gayatria (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
This research aims to investigate how the quality of service and products affects customer satisfaction at PT Bank Central Asia KCP Masjid Jamik in Pangkalpinang City. Service quality is assessed using criteria such as reliability, responsiveness, assurance, empathy, and tangible aspects, while product quality is evaluated based on its alignment with customer needs, features, and perceived benefits. The study employed a descriptive quantitative approach, collecting data from 96 customers of PT Bank Central Asia KCP Masjid Jamik in Pangkalpinang City through distributed questionnaires. Sampling was done using Probability Sampling with the Simple Random Sampling method. The analysis included tests for validity, reliability, classical assumptions, multiple linear regression, coefficient of determination (R²), as well as simultaneous (F Test) and partial (t Test) tests. The results indicate that both service quality and product quality have a significant impact on customer satisfaction at PT Bank Central Asia KCP Masjid Jamik Pangkalpinang.